Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.3346/jkms.2002.17.4.544
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Ligation of Transverse or Sigmoid Sinus in Surgery of Large Petroclival Meningiomas

Abstract: The authors present the experience of ligation of transverse or sigmoid sinus in the surgical removal of petroclival meningiomas. We reviewed the medical records and venograms of 14 patients with petroclival meningiomas, in whom the intraoperative ligation of transverse or sigmoid sinus had been done at our hospital between 1986 and 1999. All patients passed the intraoperative test clamping of the sinus. The drainage pattern of confluence of Herophili was classified into four types: type A, confluence and equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…It is contraindicated when the ipsilateral transverse sinus is hypoplastic. 9 Because our combined preand retrosigmoid approach does not require transection of the sigmoid sinus, obstruction of this sinus is not a contraindication.…”
Section: Discussionmentioning
confidence: 98%
“…It is contraindicated when the ipsilateral transverse sinus is hypoplastic. 9 Because our combined preand retrosigmoid approach does not require transection of the sigmoid sinus, obstruction of this sinus is not a contraindication.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, there is no information available regarding the frequency of incomplete mixing at the CS. In addition, when the TS or SS must be sacrificed, the likelihood of venous complications depends upon the patient's venous anatomy (Lanzieri et al, 1987;Hwang et al, 2002). However, preoperative venograms only provide information regarding the dominance of outflow sinuses, which are usually insufficient in predicting the risk of venous stasis and thus potential thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Megerian et al (1996) reported immediate or delayed complications (up to 24-48 hr), including infarction and hemorrhage, after sinus ligation and resection, even when employing intraoperative monitoring. Hwang et al (2002) suggested that regardless of TS dominance in preoperative venograms, TS or sigmoid sinus ligation is tolerable if test clamping proves to be safe. It may be expected that opening of end-to-end anastomoses of the meningeal veins to other venous channels preserves a functioning vascular drainage system, but this process demonstrates great interindividual and interhemispheric variations (Jacobs et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Hwang et al (6) it was shown that the drainage pattern of the confluence of sinuses was important for clinical decision making in the surgical removal of the large petroclival meningiomas. Fiumara et al (7) reported a case of multiple dural arteriovenous fistulas of the transverse sinuses which was treated surgically.…”
Section: Casementioning
confidence: 99%